Study on the Processing and Marketing of Cajeput Oil in Basalalae Village, Waelata District, Buru Regency - Dawan, Fahri; Lasaiba, Mohammad Amin; Leuwol, Ferdinand Salomo (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2023)
Eucalyptus melaleuca cajuputi is one of the plants that has many benefits, including being a component in various ointments and blends of warming oils. From this perspective, this research is qualitatively examined to explain the processing and marketing of white wood oil in Basalalae village, with a sample size of 15 people working as extractors. Based on the research findings, the production of white wood oil distillation in Basalalae village, Waelata District, involves several stages. These stages include harvesting the white wood, separating the white wood, distillation, purification, and finally, storage to ensure the white wood oil remains fresh and unoxidized. They produce about 4 to 5 liters of white wood oil in a single production cycle. The average income the white wood oil distillation receives in Basalalae village, Waelata District, is Rp 1,124,834. The distribution of white wood oil from Basalalae village is limited to the local area and reaches the national market. The current price of white wood oil is Rp 402,000 per liter.